Biological activity studies of some rubiaceous plants (subfamily rubioideae) and phytochemical investigation of hedyotis philippinensis / Emi Norzehan Mohamad Mahbob - Mohamad Mahbob, Emi Norzehan (2010)
In this study, the biological activities of 13 Rubioideae plants were investigated with the aim of iscovering its bioactive constituents. The assays employed were ferric thiocyanate (FTC), thiobarbituric acid (TBA) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) methods for antioxidant potential as well as Griess assay for the measurement of nitric oxide (NO) inhibition in lipopolysaccharide (LPS) and interferon-y (IFN-y)-treated RAW 264.7 cells. In the in vitro antioxidant assays including FTC, TBA and DPPH, all the tested plants exert strong antioxidant potential. Hedyotis philippinensis (leaves and stems), Spermacoce exilis and Spermacoce latifolia showed potent inhibitory activity on NO production in LPS and IFN-y-induced RAW 264.7 cells in the anti-inflammatory assay. For the second part of this study, phytochemical investigation of the leaves and stems of selected Hedyotis species, namely H. philippinensis was carried out using various chromatographic and solid phase extraction techniques to yield the major iridoid glycoside, asperuloside along with scopoletin and astragalin.